2022
DOI: 10.1530/eje-21-0899
|View full text |Cite
|
Sign up to set email alerts
|

ENDOCRINE OBESITY: Pituitary dysfunction in obesity

Abstract: Obesity, the growing pandemic of the XXI century, is associated with multiple organ dysfunction, either by a direct increase in fatty organ content or by indirect modifications related to general metabolic changes driven by a specific increase in biologic products. The pituitary gland is not protected against such a situation. Different hypothalamic-pituitary axes experience functional modifications initially oriented to an adaptive situation that, with years of obesity, turn to maladaptive dynamics that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Several endocrinological alterations have been described in patients with obesity, including a decrease in growth hormone (GH) and insulin-like growth factor (IGF-1) levels [ 5 , 6 ], hypogonadism [ 7 ], and an increase in thyroid-stimulating hormone (TSH) levels [ 8 ]. All hypothalamic–pituitary axes can be affected by obesity [ 9 ]. Despite this, the pituitary morphology in such patients is understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Several endocrinological alterations have been described in patients with obesity, including a decrease in growth hormone (GH) and insulin-like growth factor (IGF-1) levels [ 5 , 6 ], hypogonadism [ 7 ], and an increase in thyroid-stimulating hormone (TSH) levels [ 8 ]. All hypothalamic–pituitary axes can be affected by obesity [ 9 ]. Despite this, the pituitary morphology in such patients is understudied.…”
Section: Introductionmentioning
confidence: 99%
“…The on-treatment data challenge the concept that TSH elevations in PCOS relate primarily to androgen excess [18] or body weight [19, 25, 26] given that the tested treatments had virtually parallel effects on androgenemia and body weight while having markedly divergent effects on TSH, insulin resistance, and ectopic fat. The posttreatment data in PCOS patients strengthen the notion that SPIOMET has the capacity to confer broadly normalizing benefits that persist beyond its intake and that are herewith extended to include a lowering of TSH concentrations into the safest preconception range.…”
Section: Discussionmentioning
confidence: 99%
“…The present pre-, on-, and posttreatment observations corroborate the hypothesis that a TSH elevation in an adolescent girl with PCOS may in essence be no more than an epiphenomenon that points to the presence of insulin resistance within a context of lipid accumulation in ectopic depots. TSH elevations have previously been described as epiphenomena of insulin resistance and/or ectopic fat in a variety of study populations including overweight children and adolescents and also nonobese and obese women with PCOS [18‒21, 24‒31].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying causal association between TSH and obesity remains unclear ( 8 ), although obesity seems to be the cause of the rise in TSH serum levels ( 10 ). Some studies have observed a relationship between ectopic liver fat accumulation and TSH levels in adults ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating T4 was inversely associated with components of the metabolic syndrome in adults ( 5 ) and inversely associated with insulin resistance and visceral fat accumulation in children ( 7 ). Several epidemiological studies have investigated the association between thyroid-stimulating hormone (TSH) and obesity ( 8 ). As opposed to T4, TSH levels have been directly associated with waist circumference in adults ( 9 ), and it is known that an increase in body mass index (BMI), progressive central fat accumulation, and/or genetically driven BMI can cause an elevation of serum TSH ( 10 ), ( 11 ).…”
Section: Introductionmentioning
confidence: 99%